2008
DOI: 10.1101/lm.1049608
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of αCaMKII is differentially involved in new learning and unlearning mechanisms of memory extinction

Abstract: Accumulating evidence indicates the key role of ␣-calcium/calmodulin-dependent protein kinase II (␣CaMKII) in synaptic plasticity and learning, but it remains unclear how this kinase participates in the processing of memory extinction. Here, we investigated the mechanism by which ␣CaMKII may mediate extinction by using heterozygous knock-in mice with a targeted T286A mutation that prevents the autophosphorylation of this kinase (␣CaMKII T286A+/-). Remarkably, partial reduction of ␣CaMKII function due to the T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
4
32
1
Order By: Relevance
“…Our studies show that αCaMKII autophosphorylation-deficient mutants have impaired extinction and destabilization of LTM after retrieval. These observations indicate that not only formation of new memories but also modification of old memories by new experience during extinction requires the αCaMKII autophosphorylation, which is in agreement with a previous analysis of heterozygous T286A mutants (32). Furthermore, destabilization of LTM after retrieval requires αCaMKII autophosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…Our studies show that αCaMKII autophosphorylation-deficient mutants have impaired extinction and destabilization of LTM after retrieval. These observations indicate that not only formation of new memories but also modification of old memories by new experience during extinction requires the αCaMKII autophosphorylation, which is in agreement with a previous analysis of heterozygous T286A mutants (32). Furthermore, destabilization of LTM after retrieval requires αCaMKII autophosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to other studies using the CFC paradigm (e.g., Kimura et al 2008;Archbold et al 2010), we saw no spontaneous recovery of the behavioral performance after extinction training. Studies with fear conditioning to a discrete cue identified several factors that affect the resistance of extinction to recovery.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, aCaMKII has also been implicated in memory extinction. Heterozygous T286A mutants have impaired new learning induced by extinction training, whereas extinctionrelated unlearning is spared (Kimura et al 2008a).…”
Section: Camkiimentioning
confidence: 99%